Sistem Akuntansi untuk Struktur Pusat, Agen, dan Cabang: Tinjauan Literatur Sistematis - Saragih, Sri Rahayu; Nur Anita Chandra Putry; Iis Kinasih; Ratna Dwi Widariyanti (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
Companies with central, agent, and branch organizational structures face considerable complexity in managing and reporting financial information due to differences in operational functions and the wide geographical dispersion of business units. Accounting systems capable of integrating financial activities across units are therefore essential to ensure consistency in recording and the effectiveness of internal control. This study aims to systematically review the literature related to accounting systems for central, agent, and branch structures. The research employs a Systematic Literature Review (SLR) method by examining relevant scholarly articles obtained from the Google Scholar database published between 2015 and 2025. The literature selection process was conducted through identification, screening, and inclusion stages based on predefined criteria. The findings indicate that centralized accounting systems supported by integrated accounting information systems are the most commonly adopted approach for managing central–agent–branch structures. These systems play a significant role in enhancing the consistency of financial reporting, strengthening internal control, and supporting managerial decision-making. This study contributes by mapping empirical and conceptual findings on accounting systems for central, agent, and branch structures and provides a reference for future research.